Strategi Guru Profesional di Era Digital dalam Pembelajaran - Fitriani, Nur Azizah; Rusy Dina Firjanah; Erika Tia Larasati; Firma Andrian; Satria Nugraha Adiwijaya (Genderang Asa: Journal of Primary Education, 2024)
Professional teacher educator who have ability too improve the quality of learning with he experience. in the digital era it also effect to educational institutions in indonesia because it is be challenge for the teacher to provide effective quality of learning and accordance with the development of the digital. thee purpose of this research to describe the strategy used by proffesional teacher to utilize tecnology in the digital era to learning. The metode were use in this research is literature study. we search the data of this reseach with article - article Publis Or Perish with keyword “proffesional teacher and elementry learning in the digital area”. From several articles, indentification, data selection, feasibility test and data analysis. so it has 5 articles according to the literature purpose. The result from the literature have a importent point specifically to proffesional teacher in the digital era consist of three competencies: se of digital devices, use of computer application programs, teacher skill to using of application computer program for learning. Learning in the digital era to accordance with the needs of elementry school which focus on fun and entertaining of learning. Keyword: Digital Era, Proffesional Teacher, Elementry School